2016
DOI: 10.22159/ajpcr.2016.v9s3.14543
|View full text |Cite
|
Sign up to set email alerts
|

Enteric Fever in Travelers: An Updated Insight

Abstract: Enteric fever is a broad term used to represent typhoid and paratyphoid fever which is caused by S. typhi and S. paratyphi respectively. The most common cause being S. typhi, overall. However, S. paratyphi is known to infect the travelers at a higher rate. Indian subcontinent being one of the most endemic region, it is always beneficial for the travelers to get immunized while traveling to these areas. However, Vaccination to S. paratyphi is not yet available, hence travelers often fall prey to the disease. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…It is well-documented that the SEG vaccines induce protective immunity [15]. Another study [27] demonstrated that the outer membrane proteins are important to induce protective immunity against Salmonella infections. These data indicate most importantly, SEG maintains their original cell envelope and preserve immune stimulating compounds that have adjuvant properties which induce immune responses.…”
Section: Resultsmentioning
confidence: 99%
“…It is well-documented that the SEG vaccines induce protective immunity [15]. Another study [27] demonstrated that the outer membrane proteins are important to induce protective immunity against Salmonella infections. These data indicate most importantly, SEG maintains their original cell envelope and preserve immune stimulating compounds that have adjuvant properties which induce immune responses.…”
Section: Resultsmentioning
confidence: 99%
“…The FRAP method can assess antioxidant compounds that reduce the Fe 3+ complex to Fe 2+ in an acidic environment through an electron transfer process, as absorption measurements were carried out at a wavelength of 593 nm [29][30]. The mechanism of action of the FRAP method is by inactivating free radicals by electron transfer [31].…”
Section: Antioxidant Test Using the Frap Methodsmentioning
confidence: 99%